Strategi Konservasi Kebudayaan Lokal di Pesisir Selatan - Putri Bestari; Sufyarma Marsidin; Sulastri Sulastri (Departement of Mathematics Education, 2023)
This paper aims examine the strategy of preserving local culture in the South Coast to reduce the onslaught of globalization on the economy and the cultural industry. Seeing an effective strategy for developing cultural tourism based on a sense of creativity. First, identify the important factors that influence physical culture and entities by using factor and cluster analysis. Second, apply the expert's choice to implement the strategy. concluded that an important factor in cultural preservation is introducing Minang environmental culture to the community from an early age, reviving ritual traditions and preserving traditional dance and music. Third, it can be an important reference for the development of cultural tourism. An important policy is to provide cognitive, affective and conative education to the community and revive the local Pesisir Selatan culture.